Ayurvedic Management of Ashmari – A Single Case Study - Parmar, Damini; Patel, Jigna; Padadharia, Dhruval; Ninama, Divyabahen (Asian Journal of Pharmaceutical Research and Development, 2023)
Since ancient times Ashmari is mentioned in Ayurvedic texts. Ashmari is a disease related to the urinary system (Mutravahasrotas). Mutrashmari is described under Asthamahagad (difficult to cure) in Ayurveda. It possesses symptoms such as Jwara (Fever), Basti Pida (Discomfort and pain in the bladder), Aruchi (Anorexia), Mutrakriccha(Difficulty in micturition), Bastishira Vedana (Pain in Urethra), Mushka Vedana (Pain in testicles) and Shepha Vedana (Pain in the penis) have been described in Ayurvedic classical texts. A 34-year-old female patient visited OPD, with complaints of pain in the right side of the Abdomen, Burning Micturition, Nausea and Vomiting. The USG reported calculus measuring 16-17mm in right upper ureter 5mm in lower calyx of right kidney and few tiny 3-4 mm in right kidney 5-4 mm in Left kidneywith the normal functioning of vitals. The patient was treated with Chandraprabha Vati 2 BD, GokshuradiGuggulu 2 BD, Gokshurchurna +Punarnava churnaand Hajrulyahoodbhasma BD on OPD basis. The patient was advised initially follow up after 7 days and later after every 15 days. Along with medication, the patient was also advised to follow diet and lifestyle restrictions. The patient got relief in signs and symptoms and the USG report showed size of calculus decrease and some small calculi expelled.